Physical activity is associated with lower blood glucose level in high school teachers in Palu, Indonesia - Sakung, Jamaludin M.; Sirajuddin, Saifuddin; Zulkifli, Andi; Rahman, Stang Abdul; Sudargo, Toto (International Journal Of Community Medicine And Public Health, 2018)
Background: Physical activity refers to the movement of the body that causes the expenditure of energy for the maintenance of physical and mental health and is produced by skeletal muscle which is repeated over a period of time. The purpose of this research is to investigate the effect of physical activity on blood glucose level in high school teachers in Palu, Indonesia. Methods: This was a descriptive analytic research with a cross-sectional approach. The research was conducted in Palu city. Seventy-five pre-diabetic high school teachers in Palu city meeting the inclusion criteria participated in this study. Data analysis in this research was done using Ordinal Regression Test. Results: Overall, 40 respondents (53.3%) had moderate physical activity (600-1500 Mets), 32 respondents (42.7%) had heavy physical activity (>1500 Mets), and 3 respondents (4.0%) had light activity (<600 Mets). Spearman correlation test indicated a significant correlation between physical activity and blood glucose level in high school teachers in Palu City. Conclusions: Higher level of physical activity is associated with lower level of blood glucose.